Simulacro no Reino de Deus: o uso da mídia televisiva no espaço religioso da Igreja Universal do Reino de Deus como reflexo da condição pós-moderna - Basso, Nadia Garcia (2011)
The television media becomes the stage and pulpit of new religious actors, especially the neo-Pentecostal pastors who believe in the strength of this effective tool to acquire a new herd, through virtuality. The church parades on the TV catwalk. Since modern communication strategies, the Universal Church of the Kingdom of God acquired this visibility using mainly the mass media and among all projects in the area, the Rede Record TV shows to be the most ambitious. High investments occurred in the technical and programming of the station at the hearing reflected that success, at the point of taking the runner-up position in audience at various times on TV. The influence of the station is also noticed in the pews of Bishop Edir Macedo; many testimonies confess that it was through religious programming, on the Rede Record TV dawns, which led the faithful to participate in the meetings in the temples. However, the priority is not to conquer the UCKG huge audience, but to establish a contract between sender and recipient of the communication so that the viewer becomes a consumer of the religious services offered and symbolic goods. The study object of this research is the television media as an instrument of IURD disclosure of his religious ideals. It is intended to analyze the use of persuasion of the religious discourse of television IURD in the process of conversion of the faithful reconstruction of the sacred and the value proposition designed by media resources, specifically the television media. Although the theme of the Brazilian neo- Pentecostal scenario, which emerges with much impact, the Universal Church of the Kingdom of God, has been approached with a special interest for researchers in the field of Religious Science, we believe that research can establish boundaries, as where we adopt the concept of bias of Simulacrum and the Baudrillardian vision about the age of image and new technologies, the virtual and the extinction of the ideological truths , as the theoretical basis of this research in relation to the UCKG media empire in post-modernity. Delimiting the object further, we intend to examine the program say, that I listen to you from IURD so we turn to the postmodern characteristics, with special emphasis on the analysis of simulacrum that permeates contemporary television communication